QUALITY OF LIFE IN NORTH CAUCASIAN PATIENTS WITH CORONARY HEART DISEASE - R. T. Didigova; Z. Z. Bulgucheva; Z. O. Ugurchieva; A. M. Inarokova; M. N. Mamedov (Российский кардиологический журнал, 2011)
Aim. To assess the quality of life (QoL) and its gender specifics among Ingushetia Republic patients with coronary heart disease (CHD) and effort angina. Material and methods. The study included 520 patients with CHD and Functional Class II–III effort angina – 300 men (mean age 54±0,4 years) and 230 women (mean age 55,7±0,5 years). QoL was assessed with the EQ-5D questionnaire (European Quality of Life Instrument), including 5 areas: mobility, self-care, usual activities, pain/discomfort, and anxiety/depression. Results. Approximately 40% of the participants reported mobility problems, while self-care problems were reported by 15% only. Disturbed usual activities were registered in 40%, and chest pain or discomfort, as typical symptoms of effort angina, were reported by 60%. Anxiety/depression symptoms were also reported by 60% of the participants. In total, approximately 10% of the patients had severely affected QoL, while 40% did not report any difficulties with usual activities or mobility. Mobility problems, chest discomfort, and anxiety/depression were more prevalent in women. The prevalence of self-care and usual activities problems was similar in both genders. Conclusion. In every second CHD patient with effort angina, QoL was affected, due to restricted usual activities, disturbed mobility, or chest discomfort, accompanied by anxiety/depression symptoms. Self-rated health deteriorated in every second patient.